Safety of d‐ribose as a novel food pursuant to Regulation (EU) 2015/2283. (31st May 2018) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on D‐ribose as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The applicant intends to market the NF as ingredient in a variety of foods, food supplements and in certain foods for specific groups. The NF is produced by fermentation using a transketolase‐deficient strain of Bacillus subtilis and marketed as Bioenergy Ribose™. The information provided on the batch‐to‐batch variability, specifications, stability, production process and history of the organism used as a source of the NF is sufficient and does not raise safety concerns. The Panel considers that the effects observed in a subchronic toxicity study in rats could be the consequence of nutritional imbalances, but toxicological effects could not be ruled out; from this study, the Panel derived a No observed adverse effect level (NOAEL) of 3.6 g/kg body weight (bw) per day. From the human studies indicating a potential decrease in glucose levels and/or the occurrence of transient symptomatic hypoglycaemia at intakes of 10 g of d ‐ribose, the Panel defined 70 mg/kg bw per day as the NOAEL with respect to hypoglycaemia that can be considered applicable for adults. For children, the Panel acknowledges the lack of human data directly relevant for this population group. Based on the NOAEL derived from the subchronic toxicity study in rats, an acceptable level of intake of 36 mg/kg bw per day was defined that would also take into account the potentially increased sensitivity of certain population groups to hypoglycaemia. The Panel concludes that the NF is safe for the general population at intake levels up to 36 mg/kg bw per day and considers that the safety of the NF at the intended uses and use levels as proposed by the applicant has not been established.